STRATEGIES WITH AN ISLAMIC-BASED BCG MATRIX APPROACH IN SCHOOLS: Literature Systemic - Dahari, Dahari; Lestari, Dirga Ayu; Mutiara, Eka Mutiara (Jurnal Asy-Syukriyyah, 2024)
Strategic management as a series of strategic decisions that guide a company to achieve a number of organizational goals and objectives. The scope ranges from corporate values and responsibilities, managerial capabilities, to administrative systems related to strategic and operational decision-making at all levels of the hierarchy. One of the main roles of strategic management is to fully incorporate the various functional areas of the organization, as well as, to ensure these functional areas are well aligned and put together. Qualitative Research Method with Research Library, which is combining several data collection methods with pre-existing data sources. The result of this research is that In marketing, the importance of integrating Islamic values, such as honesty, trust, and justice, ensures that activities do not only focus on profit, but also on common welfare. By involving all stakeholders—teachers, students, and parents—schools can create a sense of ownership of the program, while an effective monitoring and training system ensures that Islamic values are integrated into every aspect of education.